2017
DOI: 10.1039/c6cc10158e
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange: a novel way of preparing hierarchical porous structure in poly(ionic liquid)s

Abstract: The exchange of bulky salicylate and its dimers/clusters in PILs by other smaller anions increased specific surface area and fabricated a hierarchical porous structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…To determine isolated yields, following the reaction the mixture was purified by means of flash chromatography ( n ‐hexane/EtOAc (3:1) for entries 1–3, 5, and 6, hexane/EtOAc (1:1) for entries 4 and 7). Cyclic carbonates were characterized in accordance with literature data [92, 93] …”
Section: Methodsmentioning
confidence: 99%
“…To determine isolated yields, following the reaction the mixture was purified by means of flash chromatography ( n ‐hexane/EtOAc (3:1) for entries 1–3, 5, and 6, hexane/EtOAc (1:1) for entries 4 and 7). Cyclic carbonates were characterized in accordance with literature data [92, 93] …”
Section: Methodsmentioning
confidence: 99%
“…The adsorption peaks of imidazolium ring skeleton were found at 1567 and 1550 cm −1 , and C–N stretching bands of imidazolium ring were found at 1162 cm −1 . The appearance of two major peaks at 1580 and 1413 cm −1 in P[VBIM][OAc]‐10%, which were assigned to carboxylate group and C−H bending vibrations in acetate group, clearly suggested that the Br − had replaced by acetate group . Other PILs with different 3‐substituents and cross‐linker density showed analogous characteristic peaks (Figure S2 and S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 88%
“…Subsequently, the 3‐[2‐(nitrooxy)ethyl]‐1‐vinylimidazolium bromide, AIBN (0.164 g, 1.0 mmol), and methanol (17 mL) were charged into a Schlenk flask equipped with a magnetic stirrer, and the mixture was refluxed under nitrogen for 24 h. After polymerization, the polymers were cooled to room temperature, washed with ethyl acetate and methanol, and dried under vacuum to afford poly{3‐[2‐(nitrooxy)ethyl]‐1‐vinylimidazolium bromide} in 77 % yield. Anion‐exchange reactions were carried out according to the literature procedure with a minor modification …”
Section: Methodsmentioning
confidence: 99%
“…After the reaction mixture was stirred for 0.5 h, the precipitate was collected by centrifugation, washed with distilled water and dried under vacuum to affordt he E-PIL-H-3 in 42 %yield. [25] Poly{3-[2-(nitrooxy)ethyl]-1-vinylimidazolium bromide} (1.315 g, 5mmol based on monomer) was added to as aturated aqueous solution of sodium nitrate (15 mL). After stirring the reaction mixture for 24 h, the precipitate was collected by filtration and was then was added to af resh saturated aqueous solution of sodium nitrate (15 mL).…”
Section: Synthesis Of E-pilsmentioning
confidence: 99%